Bioadhesive metal–phenolic nanoparticles for enhanced NIR imaging-guided locoregional photothermal/antiangiogenic therapy. Issue 23 (2nd June 2021) - Wang, Xiuxia; Li, Hongyu; Meng, Fanling; Luo, Liang
Abstract : An adhesive nanoparticle-based drug delivery system incorporating tannic acid and Fe ions has been developed, which enables efficient NIR imaging-guided locoregional combined photothermal and antiangiogenic cancer therapy. Abstract : Locoregional drug delivery has emerged as a promising solution to the problems associated with intravenously administered antitumor agents, such as systemic toxicity and insufficient drug accumulation at tumor sites. Herein, we have developed an adhesive nanoparticle (NP)-based drug delivery system, using natural bioadhesive tannic acid (TA) and metal ions (Fe 3+ ), for locoregional photothermal and antiangiogenic synergistic cancer therapy. In this study, a new near-infrared (NIR) photothermal agent indocyanine green (IR820) and an antiangiogenic agent sorafenib (SRF) were co-encapsulated in a TA–Fe complex (SIF@TA–Fe). The SIF@TA–Fe NPs exhibited super adhesion, antiangiogenesis, and efficient cellular uptake. Moreover, SIF@TA–Fe NPs showed a synergistic antitumor effect in vivo, including high tumor inhibition rate, excellent survival extension, and low risk of recurrence, resulting from the prolonged retention of the NPs in the tumor. Thus, this adhesive SIF@TA–Fe NP-based therapeutic system provides a promising approach for locoregional drug delivery of combined cancer therapy.